PENGEMBANGAN PROFESIONALISME GURU DALAM MEWUJUDKAN KUALITAS PENDIDIKAN - RIDWAL TRISONI (Ta'dib, 2011)
Teacher plays strategic roles in realizing qualified human resources. Any attempts made in improving human resources quality without involving teacher will end in difficulties since the teacher is the key persons in determining the quality of education. Consequently, teachers are expected to have professionalism by mastering such competencies as pedagogic, professional, social and personal. To ensure the mastery of those competencies, various programs need to carry out. Among the programs are: teacher’s professional improvement must be started from teacher’s training institution (LPTK), by sending teachers higher level, in-service training, and educational supervision.Kata kunci: profesionalisme, guru, kualitas